Shari'ah review function and its implementation in Malaysia takaful companies : a practical appraisal - Mohamed Hadi bin Abd Hamid (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
This thesis aims to examine the fundamentals of Sharī'ah review function as part of Sharī'ah governance for the Islamic financial institutions in Malaysia, particularly the takāful operators. This includes examining the legal and regulatory framework of Sharī'ah review function specifically within takāful operators. Afterwards, the research attempts to study the state of implementation of Sharī'ah review function in takāful operators by highlighting the prevailing issues surrounding its implementation in takāful operators. These pressing issues are established based on current laws and regulations, existing literatures, fieldwork study and available findings. Based on the findings, the thesis revealed that the implementation of Sharī'ah review function in takāful operations is surrounded with several existing problems which ranges from the issue of availability of dedicated Sharī'ah review officers to the issue of commitment portrayed by the management and Sharī'ah Committee of takāful operators in supporting the execution of Sharī'ah review function. While these problems may hamper the robust implementation of Sharī'ah review function, the thesis provides recommendations to the regulator and relevant parties to mitigate or remove the problems with a view to ensure Sharī'ah compliance in the operation and business activities of takāful operators.